PENERAPAN METODE PEMBERIAN TUGAS UNTUK MENINGKATKAN KEMAMPUAN MEMBACA NYARING SISWA KELAS IV SD NEGERI 013 PAGARAN TAPAH DARUSSALAM - Kelana ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research is motivated by the lack of ability to read aloud the fourth grade primary school013 Pagaran Tapah Darussalam. This study aims to improve the ability to read aloud usingthe method of giving the task to improve the ability to read aloud the fourth grade students ofSD Negeri 013 Pagaran Tapah Darussalam. Subjects of this study is the fourth grade studentsof SD Negeri 013 Pagaran Tapah Darussalam totaled 20 students, consisting of 10 femalestudents and 10 male students in the academic year 2014-2015. Form of research isclassroom action research. The research instrument consists of instruments and instrumentperformance data collection activity observation sheet form teacher and student activity.Based on the results of the research shows that the students' skills in reading aloud increased.It is known from preliminary data the average value of 63.2. When viewed from the classicalcompleteness, there are 19.2% of students (5 persons) who finished obtaining a minimumvalue of 70 (according to the standard KKM). However, after the implementation of themethod of assignment, obtained an average value of 68.9 or completeness of 50% of students(13 people). Then in the second cycle, to reach an average value of 81.4 or completeness of100%. Thus, this study is said to been able to.